(untitled) (Scientific journal of the Fergana State University, 2025)
In history, the program known as the "Kasigin Course," recognizing the leading role of industry in production, proposes a refined and comprehensive system for the integrated economic uplift of the national economy. The impact of these reforms on the agricultural sector of Uzbekistan has led to a series of changes in the industry, opening new directions and opportunities. This article explores the process of implementing these reforms in agriculture.